Legislasi Hukum Kewarisan Islam Menuju Hukum Nasional: Analisis Nilai-Nilai Keadilan Dalam Masyarakat Bacukiki Parepare - Fikri Fikri; Andi Bahri; Budiman Budiman (Al-Risalah, 2017)
This research about Islamic law is as the applicable and acceptable law in Indonesian society. Islamic law placed inheritance law to regulated directly with the problems of socio-cultural in community, using the theological normative, yuridical and sociological approach. However, the Islamic inheritance lawstill regulated in the Instruction President Number 1, 1991 on KHI. The enforcement of KHI has not given satisfaction among Muslims including Islamic jurists. It caused the existence of KHI was not placed in the hierarchy of legislation Indonesia. Nowdays, the spirit of Islamic Indonesian society in order that the Islamic inheritance law will be legislated as well as marriage law. Even though, when the application of the Islamic inheritance law in the form of legislation as national law, the principle of justice should be Implemented in human life, family and society, even nation life.